Enhanced oxygen reduction with single-atomic-site iron catalysts for a zinc-air battery and hydrogen-air fuel cell - Yuanjun Chen (Nature Portfolio, 2018)
Development of fuel cells and metal-air batteries is hindered by electrocatalyst performance, which can be enhanced with uniform and atomically dispersed active sites. Here the authors report an iron-based electrocatalyst for oxygen reduction in cathodes for a zinc-air battery and a hydrogen-air fuel cell.